Power Conditioning with Electric Car Battery Charging from Renewable Sources (Hungarian Journal of Industry and Chemistry, 2010)
A control method for electric car battery charging combined with small domestic power plants using renewable energy is described in this paper. This method is not only capable of optimizing the working point and charging current of the system but also implements robust energy flow control to balance the convenient process variables.The proposed controller has been investigated by simulation in Matlab environment, and as a result, succesful combination of a grid synchronised inverter and a electric car battery charger robust operation could be achieved in changing operational modes.